Notes on the systematic value of the tongue morphology in different genera and species groups of lacertid lizards (Reptilia: Lacertidae) - Cei, José Miguel Alfredo María (1996)
The tongue shape and its epidermal structure was examined in a stock of palearctic and paleotropical lizards from Europe, Africa, the Middle East and south eastern Asia. The results of this preliminary report clearly point out the systematic importance of this morphological feature in providing valuable generic and specific characters. The fundamental pattern described for the genera Podarcis, Lacerta sensu stricto and Gallotia, e. g., is very distinctive despite several features in common, likely due to ancient phyletic relationships. A number of similar morphological trends stress the reciprocal affinities between Lacerta (Archaeolacerta) and the widely spread genus Podarcis which is still undergoing speciation. Another case is the minor but significant affinities linking the genera Lacerta sensu stricto and Gallotia, the latter also undergoing more complicated speciation due to its insular isolation. The interspecific differences in the taxa belonging to the so-called “species groups” such as Podarcis, are scanty or insignificant. Instead there are striking differences in the generic patterns of the tongue morphology in Afro-Asian lacertid lizards. However, a similar pattern was found in the African genera Adolfus and Holaspis or Centromastix (= Gastropholis according to Arnold, 1989) and Ichnotropis.